Relations Of Vaginal Bacterial Infection Types Based On Gram Staining With Premature Rupture Of Membranes - Bayu Permana; Ariadi Ariadi; Joserizal Serudji (Syntax Literate, 2022)
Introduction: Premature rupture of membranes (PROM) is defined as rupture of the membranes before delivery (<37 weeks is called preterm premature rupture of membranes-PPROM, >37 weeks is called premature rupture of membranes-PROM). PPROM complicates 3-8% of pregnancies and is responsible for 20-30% of all preterm births and perinatal morbidity. Bacterial infection in the third trimester of pregnancy is a risk factor for PROM. Vaginal infections originate from pathogenic microorganisms that interfere with the normal vaginal flora. The microorganism causing the infection can usually be found by Gram stain and/or vaginal swab culture. Objective: To determine the relationship between vaginal bacterial infection based on Gram stain and the incidence of preterm premature rupture of membranes. Methods: This study is observational with a cross-sectional comparative study design. Sampling was conducted from Mei 2020 hingga April 2021. A total of 60 pasien preterm who met the criteria were investigated, with 30 samples experiencing PROM and 30 samples not experiencing PROM. Every sample was performed vaginal swab to examine the existence of bacterial infection based on Gram stain. The chi-square test was used for statistical analysis. Results: The most recent education level was SMA (PPROM 57%, non-PPROM 63%). Most were multiparous (PPROM 73%, non-PPROM 67%) and delivered by cesarean section (PPROM 70%, non-PPROM 90%). 63.3% of patients had vaginal infections (PPROM 90%, non PPROM 63.3%). Most infections are caused by gram negative bacteria. The results of statistical tests showed that there was a significant relationship between bacterial infection and the incidence of preterm premature rupture of membranes (p<0.05) but there was no significant relationship between bacterial species based on vaginal Gram staining and the incidence of preterm premature rupture of membranes (p >0.05). Conclusion: Gram stain examination should be carried out routinely as an initial procedure for treating PROM patients so that it can be a guide for selecting the right antibiotic therapy in future studies.